REINTERPRETASI SIMBOL BATIK DEMAK - afrizal, afrizal (Acintya, 2019)
AbstractThis article wants to reinterpret the symbol of batik Demak that has been lost for hundreds of years. Demak as the first Islamic empire, in its time, becomes the center of Islamic Javanese culture and a cultural figure with the various cultural products. One of the cultural products in Demak is batik. The context of this study views Batik Demak as a cultural form, namely artifacts that contain a discourse of self-representation found by ideographic aspects of the initiator and the culture that produce to it. This discourse is reflected in the form or figure of the object as well as the implicit meaning. Batik Demak is considered to be a cultural heritage in Demak since hundreds of years ago. It had, once, disappeared then in 2006 it was reappeared. This must cut the strings of history about the meaning and function of Batik Demak in ancient times. Batik Demak tends to present when each region in the territory of Indonesia, especially Central Java is promoting batik with regional motifs. The reinterpretation of symbols that emerge seems to be a strategy of branding or imaging an area. The meaning of the symbol of batik does not really represent the pattern of life of Demak community as manifested in the five typical motives of Demak.Keywords: Batik Demak, Reinterpretation, Symbols